Retrospective serological study of Rickettsia spp. and Borrelia spp. antibodies in patients with peripheral facial nerve palsy. Issue 1 (1st January 2021) - Wallménius, Katarina; Påhlson, Carl; Nilsson, Kenneth
ABSTRACT: In a retrospective study, 36 patients with peripheral facial palsy were serologically evaluated for the presence of Rickettsia spp. and Borrelia spp. antibodies. All sera underwent immunofluorescence and Western blot analysis for IgG and IgM antibodies using Rickettsia helvetica and R. felis as antigens. Anti- Borrelia antibodies were detected using a commercial ELISA detecting Borrelia burgdorferi, B. afzelii and B. garinii . Three patients (8.3%) were seropositive for Rickettsia spp. with IgG titres equal to 1:128, and six patients (16.7%) had IgM titres equal to or above 1:128. All samples with IgG/IgM titres equal to or above 1:128 were confirmed by Western Blot. Four patients (11.1%) had IgG antibodies against Borrelia at a titre level normally judged to be indicative of current infection. Two of these patients had significant IgG or IgM titres for both Rickettsia spp. and Borrelia spp., indicating co-infection. In conclusion, the findings indicate current rickettsial infection or early response at about the same degree as for Lyme borreliosis in patients with facial palsy, but they need to be further examined with a larger number of patients and paired serum analyses.